All-Arthroscopic Intratendinous Dermal Patch Integration for Large-Sized Rotator Cuff Tear - Sreejith Thampy J., M.S. Ortho; Yon-Sik Yoo, M.D., Ph.D.; Ayyappan V. Nair, D.N.B., M.N.A.M.S. (Arthroscopy Techniques)
Patch augmentation of rotator cuff repair can create a healed tendon-bone interface, rather than the formation of a fibrovascular scar tissue, seen even after maximizing biomechanical strength of repair with a double-row construct. Here we describe our technique of patch interposition between the tendon and bone interface. Most arthroscopic patch augmentation techniques are challenging, and here we present a simpler reproducible approach, which has minimal strain on tissue and repair construct without compromising on the footprint coverage.